성인 환자에서 위와 결장에 동시 침범한 랑게르한스 세포 조직구증: 증례 보고 - 김성제; Seong Je Kim; 하세인; Se In Hah; 곽지윤; Ji Yoon Kwak; 최정우; Jung Woo Choi; 조현진; Hyun Chin Cho; 하창윤; Chang Yoon Ha; et al. (The Korean journal of gastroenterology, 2022)
Langerhans cell histiocytosis (LCH) is reported less frequently in adults than in children. The most common site of involvement in adults is the bone, accounting for 30-50% of cases. The gastrointestinal tract is very rare, accounting for approximately 2%. We present a case of Langerhans cell histiocytosis that simultaneously invaded multiple organs, including the stomach and colon, in an adult. A 37-year-old woman with no underlying disease complained of chest discomfort and a palpable right submandibular mass. A right Level II neck mass and mediastinal LN enlargement were confirmed on the pharynx and chest CT scan. Multiple subepithelial masses with central ulceration and erosion were observed in the corpus and fundus on the esophagogastroduodenoscopy and in the right colon on the colonoscopy. The histopathology findings were the same in each tissue biopsied from the stomach, colon, and right neck lymph nodes. Langerhans cells with classical reniform nuclei and prominent eosinophils invaded the normal glands, and S100 and CD1a were positive in the immunohistochemical stain. Gastrointestinal involvement of LCH in adults is rare, asymptomatic,and can involve multiple digestive organs simultaneously, so upper endoscopy and colonoscopy should be considered for a diagnosis. (Korean J Gastroenterol 2022;80:149-153)